Attributional Accuracy and Leadership Effectiveness: Cultural Desirability in Five Countries - Lakshman, C.; Vo, Linh-Chi; Gok, Kubilay (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
The literature on the cultural desirability of accurate attributions of leaders is non-existent. In addition, the attributional theories of leadership literature focus primarily on biased attributions. We contribute to these two literatures by providing an empirical examination from five countries (USA, France, India, Turkey, and Vietnam), using implicit leadership theory approach. We examine two characteristics of the attributions – degree of accuracy, and degree to which they are free of racial/cultural bias – which managers make for subordinate behavior in the performance domain to assess whether or not they are isomorphic with cultural expectations and thereby constitute desirable leadership.